2015
DOI: 10.1016/j.drup.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteasome deubiquitinase activity: a strategy to overcome resistance to conventional proteasome inhibitors?

Abstract: The ubiquitin-proteasome system (UPS) is the primary mechanism controlling the degradation of damaged, unwanted or short-lived proteins in eukaryotic cells. In addition to protein homeostasis, the UPS has also emerged as a critical node in the regulation of signalling pathways implicated in the growth and survival of cancer cells. The absolute dependency of cancer cells on a functioning UPS has been exploited in the development of anti-cancer therapies as exemplified by development of proteasome inhibitors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 109 publications
2
31
0
Order By: Relevance
“…It is well established that inhibition of DUBs or the proteasome causes accumulation of ubiquitinated proteins [35]. Like in other cancer cells, we previously reported [27], we found that NiPT dose- and time-dependently induced accumulation of ubiquitinated proteins (Ubs) and proteasome substrate protein p27 in all CML cell lines we detected before the emergence of PARP cleavage (Fig.…”
Section: Resultssupporting
confidence: 76%
“…It is well established that inhibition of DUBs or the proteasome causes accumulation of ubiquitinated proteins [35]. Like in other cancer cells, we previously reported [27], we found that NiPT dose- and time-dependently induced accumulation of ubiquitinated proteins (Ubs) and proteasome substrate protein p27 in all CML cell lines we detected before the emergence of PARP cleavage (Fig.…”
Section: Resultssupporting
confidence: 76%
“…USP14 and UCHL5 are cysteine proteases associated with the 19S regulatory subunit of the proteasome, with overlapping and sometimes complementary roles. Because of their slightly different deubiquitinating profiles, USP14 can either rescue proteins from proteasomal degradation by removing the polyubiquitin chain that facilitates proteasomal interaction or simply recycle the ubiquitin from a protein already commited to proteasomal interaction while UCHL5 more frequently facilitates proteasomal degradation [4850]. However, these two structurally distinct deubiquitylases have overlapping and partially redundant functions so that they can compensate for each other’s activity [51, 52], as we have observed here.…”
Section: Discussionmentioning
confidence: 83%
“…455,456,458 Multitarget combination treatment Drug adverse effects and resistance are major obstacles in preclinical and clinical cancer treatments, and UPS inhibitors are no exception. [459][460][461] For drug adverse effects, the balance between effective dose and dose limiting toxicity is the principal contradiction. 462 The molecular mechanisms of anti-cancer drug resistance are also associated with tumor metabolism, the TME and CSCs, such as increasing drug metabolism and degradation of drug target proteins, enhance the tolerability of stressful TME conditions, and enhance the DNA damage response and antiapoptotic mechanisms of CSCs.…”
Section: Targeting E3 Enzymesmentioning
confidence: 99%